Distinct roles for TET family proteins in regulating human erythropoiesis - Yan, Hongxia; Wang, Yaomei; Qu, Xiaoli; Li, Jie; Hale, John; Huang, Yumin; An, Chao; Papoin, Julien; Guo, Xinhua; Chen, Lixiang; Kang, Qiaozhen; Li, Wei; et al. (Blood, 2017)
The ten-eleven translocation (TET) family of proteins plays important roles in a wide range of biological processes by oxidizing 5-methylcytosine (5mC) to 5-hydroxy-methylcytosine. However, their function in erythropoiesis has remained unclear. We show here that TET2 and TET3 but not TET1 are expressed in human erythroid cells, and we explore the role of these proteins in erythropoiesis. Knockdown experiments revealed that TET2 and TET3 have different functions. Suppression of TET3 expression in human CD34+ cells markedly impaired terminal erythroid differentiation, as reflected by increased apoptosis, the generation of bi/multinucleated polychromatic/orthochromatic erythroblasts, and impaired enucleation, although without effect on erythroid progenitors. In marked contrast, TET2 knockdown led to hyper-proliferation and impaired differentiation of erythroid progenitors. Surprisingly, knockdown of neither TET2 nor TET3 affected global levels of 5mC. Thus, our findings have identified distinct roles for TET2 and TET3 in human erythropoiesis, and provide new insights into their role in regulating human erythroid differentiation at distinct stages of development. Moreover, because knockdown of TET2 recapitulates certain features of erythroid development defects characteristic of myelodysplastic syndromes (MDSs), and the TET2 gene mutation is one of the most common mutations in MDS, our findings may be relevant for improved understanding of dyserythropoiesis of MDS. •TET3 knockdown impairs terminal erythroid differentiation, whereas TET2 knockdown leads to accumulation of erythroid progenitors.•Global levels of 5mC are not altered by knockdown of either TET2 or TET3.